Pengembangan Instrumen Asesmen Keterampilan Teknologi dan Media Informasi pada Mata Pelajaran Fiqih Bab Waris - Hidayatulloh, Muhammad Kris Yuan; Nidia, Aulifia Faj'ri; Ashoumi, Hilyah (Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this study was to produce a skill assessment instrument that can train students in dealing with current technological developments which can then be applied in inheritance and knowing students responses to the product developed. The research uses Research and Development (RnD) research with a 4-D design which consists of 4 stages, namely defining, designing, developing, and disseminating with class XI MA as the subject. The data analysis techniques use validity (0,361) and reliability tests. The results of this development research were declare suitable for use based on an average expert validation of 79,06%. The validity tests showed that the > (0,361) and Cronbach’s Alpha from the Reliability test was 0,947 > the reliability coefficient was (0,6). As for the student responses to the developed product is has a value of 51,9 so that if it matched with the assessment criteria table, the response has a very good category.